Hacelia superba H. L. Clark, 1921 and Chaetaster longipes Retzius, 1805 (Echinodermata: Echinodea) new records for Canary islands. - Garrido, M. J. (2004)
During the 2003 SEGA expeditions one individual of Chaetaster longipes Retzius, 1805 was found at 40 meters depth by a SCUBA diver at Los Islotes (North Lanzarote), and two individuals of Hacelia superba Clark, 1921 were caught respectively by a circular wire fish trap and by dredging northeast of Gran Canaria. These are first records for the infralittoral and circumlittoral zones of the Canary Islands.